Common Ground on Hostile Turf Stories from an Environmental Mediator - Moore, Lucy.; SpringerLink (Online service) (Washington, DC : Island Press/Center for Resource Economics : Imprint: Island Press, 2013)
In our increasingly polarized society, there are constant calls for compromise, for coming together. For many, these are empty talking points$1 (Bfor Lucy Moore, they are a life's work. As an environmental mediator, she has spent the past quarter century resolving conflicts that appeared utterly intractable. Here, she shares the most compelling stories of her career, offering insight and inspiration to anyone caught in a seemingly hopeless dispute. Moore has worked on wide-ranging issues$1 (Bfrom radioactive waste storage to loss of traditional grazing lands. More importantly, she has worked with diverse groups and individuals: ranchers, environmental activists, government agencies, corporations, tribal groups, and many more. After decades spent at the negotiating table, she has learned that a case does not turn on facts, legal merit, or moral superiority. It turns on people. Through ten memorable stories, she shows how issues of culture, personality, history, and power affect negotiations. And she illustrates that equitable solutions depend on a healthy group dynamic. Both the mediator and opposing parties must be honest, vulnerable, open, and respectful. Easier said than done, but Moore proves that subtle shifts can break the logjam and reconcile even the most fiercely warring factions. This book should be especially appealing to anyone concerned with environmental conflicts; and also to students in environmental studies, political science, and conflict resolution, and to academics and professionals in mediation and conflict resolution fields.s
Preface -- Acknowledgments -- Chapter 1. Introduction -- Chapter 2. Encountering Hostile Turf -- Chapter 3. The Power of Story -- Chapter 4. Sheep in the Wilderness -- Chapter 5. Finding Common Ground -- Chapter 6. The Army Corps Takes Orders -- Chapter 7. A Rugged Road -- Chapter 8. So Close to Consensus -- Chapter 9. When the Past Won$1 (Bt Go Away -- Chapter 10. When Cookies Aren$1 (Bt Enough -- Chapter 11. Tribes Take the Lead -- Chapter 12. Conclusion -- About the Author -- Index.s
Keywords: Environmental sciences; Environmental law; Environmental toxicology; Pollution; Environment; Environmental Law/Policy/Ecojustice.; Communication Studies; Social Structure, Social Inequality; Pollution, general; Ecotoxicology